Boost in internal quantum efficiency of AlGaN-based deep ultraviolet multiple quantum wells by using multifaceted localization structures - Ge Gao; Li Chen; Yirong Yao; Ming Li; Weiguang Yang; Wei Guo; Jichun Ye (Applied Physics Express)
This study demonstrates AlGaN multifaceted multiple quantum wells (MQWs) with a significantly enhanced localized emission, achieved through anisotropic growth control in migration-enhanced metal-organic chemical vapor deposition. By precisely regulating in-plane growth kinetics, pit-free semipolar sidewalls with tailored microstructures MQWs were obtained, leading to optimized emission properties. Scanning Auger Nanoprobe analysis revealed Ga-rich apex regions within the microfacets, which directly correlated with the enhanced localized emission observed in cathodoluminescence mapping. The multifacet structure exhibits remarkable enhancement in emission intensity through carrier redistribution. A quasi-internal quantum efficiency of 93.9% was achieved, making a significant milestone in the development of semipolar AlGaN MQWs.